The wealth of nations : vision and conceptualization - Ranadive, K. R. (Working paper (Centre for Development Studies (Trivandrum, India)) ;, 1976)
In the context of The wealth of nations, work on economics, by Adam Smith, 1723-1790, Scottish economist and philosopher.